Influence of acidic properties of different solid acid catalysts for glycerol acetylation - Dalla Costa, Bruno Oscar (2017)
The glycerol esterification with acetic acid is studied in this work using propylsulfonic functionalizedmesoporous silica (Pr-SO3H-SBA-15), and compared with H-ZSM-5 and H-Beta zeolites. The reactionwas carried out in a batch reactor using a 6:1 molar ratio of acetic acid to glycerol. The initial TOF for theglycerol conversion was significantly higher in the propylsulfonic mesoporous silica, as compared to thetwo zeolites. These two catalysts have acid sites densities (mol m−2) that are less than half than thatdisplayed by the SBA-based catalyst. It was possible to obtain 96% conversion in 2.5 h, with 87% selectivityto the products of interest diacetylglycerol (DAG) + triacetylglycerol (TAG), being the ratio DAG/TAG = 1.7.The catalyst deactivates partly due to sulfonic groups loss and to coke deposition during the reaction,as observed when it was used in a second reaction cycle without any treatment in between cycles. Thecatalyst lost activity, but maintained the selectivity, associated to a non-selective site poisoning.